Experimental investigations of hardening and heating processes of large steel industrial ingots - I. A. Samojlovich; V. I. Timoshpolsky; A. B. Steblov; I. A. Trusova; R. B. Vais; V. V. Nesvet (Литьë и металлургия, 2001)
Experimental investigation techniques of thermal condition during hardening and heating of large steel ingots made in industrial conditions with account of specific features of production organization and heating units are worked out. Regularities of hardening and heating of blooming and slab ingots are analyzed.